Capital-labor distortions in project finance - Martin Peitz; Dongsoo Shin (University of Mannheim, Department of Economics, 2015)
An entrepreneur needs a lender's capital input to finance a project. The entrepreneur, who is privately informed about the project environment, provides a labor input (effort). Capital and labor are perfect complements. We show that the entrepreneur may optimally distort the project's capital-labor ratio. The direction of the distortion in capital-labor ratio depends on contractibility of the entrepreneur's labor input. If the entrepreneur's labor input is contractible, in the optimal contract, the entrepreneur may provide an excessive amount of labor for the amount of capital funded by the lender. If, by contrast, the entrepreneur's labor input is non-contractible, part of the physical asset funded by the lender may remain idle.
urn:nbn:de:bsz:180-madoc-373888
Keywords: D82; D86; G31; 330; Agency; Project Finance; Capital-Labor Ratio; Contractibility